2021
DOI: 10.1155/2021/4218086
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Frequency Electrical Stimulation Promotes Satellite Cell Activities to Facilitate Muscle Regeneration at an Early Phase in a Rat Model of Muscle Strain

Abstract: The capability of regeneration for skeletal muscle after injury depends on the differentiation and proliferation ability of the resident stem cells called satellite cells. It has been reported that electrical stimulation was widely used in clinical conditions to facilitate muscle regeneration after injury, but the characterization of satellite cell responses to the context of low-frequency electrical stimulation in early-phase muscle strain conditions has not been fully clarified. In this study, we aim to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This is the rst study to examine the effects of ES during prolonged MV using genetic analysis of the diaphragm muscle. Although there have been numerous studies related to ES-induced effects on muscle atrophy 21,23,24 , no study has analyzed the genetic changes caused by ES during prolonged MV. The main ndings of the present study are that 12-hour MV is reasonable for establishing a VIDD rat model and that ES favorably affects genes related to in ammatory cytokines, skeletal muscle, and internal respiration (oxygen transport and mitochondrial respiration) during prolonged MV.…”
Section: Discussionmentioning
confidence: 99%
“…This is the rst study to examine the effects of ES during prolonged MV using genetic analysis of the diaphragm muscle. Although there have been numerous studies related to ES-induced effects on muscle atrophy 21,23,24 , no study has analyzed the genetic changes caused by ES during prolonged MV. The main ndings of the present study are that 12-hour MV is reasonable for establishing a VIDD rat model and that ES favorably affects genes related to in ammatory cytokines, skeletal muscle, and internal respiration (oxygen transport and mitochondrial respiration) during prolonged MV.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that skeletal muscle-resident stem cells (also known as muscle satellite cells) contribute to muscle regeneration in response to various injuries [40][41][42][43][44][45][46][47]. However, a previous study demonstrated that lifelong reduction of satellite cells neither accelerated nor exacerbated sarcopenia and that satellite cells did not contribute to the maintenance of muscle size or fiber type composition during aging, but that their loss may contribute to age-related muscle fibrosis [48].…”
Section: Discussionmentioning
confidence: 99%